A 3D Polyoxometalate‐Based Framework Constructed from Ag/trz Metal‐Organic Ribbons and P2W18 Polyoxoanions: Synthesis, Structure and Electrochemical Properties1. Issue 10 (3rd June 2015) - Wang, Xiang; Zhang, Rui; Tian, Aixiang; Wang, Xiuli
Abstract A Wells‐Dawson Polyoxometalate‐based hybrid, Ag9(trz)3(Htrz)4 (H2O)(P2W18O62)·3H2O (1) (Htrz = 1, 2, 4‐1H‐triazole) was hydrothermally synthesized through using trz ligand and silver nitrate in the presence of [P2W18O62]6– polyoxoanion. In the 3D framework structure of compound 1, two kinds of wave‐like Ag/trz chains originated from trz ligands and silver cations are aggregated in a "2+1" mode by {Ag2/trz} linkages to result in a 1D Ag/trz metal‐organic ribbon, which is further extended into a 3D framework structure by [P2W18O62]6– polyoxoanions through Ag‐O covalent bonds. Additionally, the electrochemical properties of compound 1 have also been investigated.